Daclatasvir plus asunaprevir for HCV genotype 1b infection in patients with or without compensated cirrhosis: a pooled analysis. (24th January 2016) - Kao, Jia‐Horng; Jensen, Donald M.; Manns, Michael P.; Jacobson, Ira; Kumada, Hiromitsu; Toyota, Joji; Heo, Jeong; Yoffe, Boris; Sievert, William; Bessone, Fernando; Peng, Cheng‐Yuan; Roberts, Stuart K.; et al.
Abstract: Background & Aims: We compared outcomes by cirrhosis status across studies of the all‐oral combination of daclatasvir (DCV) plus asunaprevir (ASV). Methods: Outcomes from global and Japanese phase 2 and 3 clinical studies of DCV+ASV in patients with genotype (GT) 1b infection were assessed by cirrhosis status. Sustained virological response (SVR) was assessed in individual phase 3 studies; a pooled analysis was carried out for safety outcomes. Results: In the Japanese phase 3 study, SVR12 was achieved by 91% of patients with cirrhosis ( n = 22) and 84% of patients without cirrhosis ( n = 200); in the global phase 3 study, SVR12 was achieved by 84% of patients with cirrhosis ( n = 206) and by 85% of patients without cirrhosis ( n = 437). The frequency of serious adverse events, adverse events leading to treatment discontinuation and treatment‐emergent grade 3/4 laboratory abnormalities was low (<10%) and similar among patients with ( n = 229) or without ( n = 689) compensated cirrhosis receiving DCV+ASV. Grade 3/4 reductions in platelets and neutrophils were more common among patients with cirrhosis (1.3 and 2.2%, respectively) compared with those without cirrhosis (both 0.6%). Grade 3/4 liver function test abnormalities were less common among patients with cirrhosis (1.8%) compared with those without cirrhosis (3.5–4.7%). Alanine aminotransferase elevations were not associated with hepatic decompensation. Conclusions: The safety and efficacy of DCV+ASV were similar in patients with or without compensated cirrhosis. This all‐oral, interferon‐ and ribavirin‐free combination is an effective and well‐tolerated treatment option for patients with HCV GT1b infection and cirrhosis. Trial registrations numbers:Clinicaltrials.gov identifiers: NCT01012895; NCT01051414; NCT01581203; NCT01497834.